Chinese ways of being good Muslim: from the Cheng Hoo Mosque to Islamic education and media literacy - Rahmawati Rahmawati; Kasim Yahiji; Choirul Mahfud; Jauharoti Alfin; Much Koiri (IAIN Salatiga, 2018)
This article aims to explore the Chinese ways of being Muslim, from buildingthe Cheng Hoo mosque to serving Islamic education and media literacy. Inthe current millennial disruption era, the role of communication medialiteracy in the contemporary Indonesian Chinese Muslim community needsto be studied further, especially its role in supporting the status of being goodChinese Muslim. This article is also intended to discuss the Chinese ways offostering converts and Chinese Muslims through both communication medialiteracy and information technology literacy. Through media analysis method,communication media literacy is part of communication which is based on whosays what, in which channel, to whom, with what effects. This research finds outthat communication media literacy is used by the Indonesian Chinese Muslimcommunity through the publication of Cheng Hoo magazine, WhatsApp ForumPITI Jatim, website, and Facebook. All of these media are used and have asignificant effect on the relation, interaction, aspiration, and communicationbetween the Chinese Muslim community and Chinese non-Muslim community,and the Chinese Muslim community with non-Chinese Muslims in Indonesia.Moreover, the Chinese ways of being good Muslims could also be understoodfrom various ways in establishing Cheng Hoo Mosque, Islamic educationservices based on Chinese community from Kindergarten, Islamic ElementarySchool, Pesantren, and routine or regular discussions.Artikel ini bertujuan untuk mengeksplorasi bagaimana cara-cara orangTionghoa menjadi Muslim dari upaya pembangunan masjid Cheng Hoo hinggapelayanan pendidikan Islam dan literasi media. Di era disrupsi milenial sepertisaat ini, peran literasi media komunikasi dalam komunitas Tionghoa Muslimdi Indonesia kontemporer perlu dikaji lebih lanjut, khususnya perannya dalammendukung menjadi muslim Tionghoa yang baik. Paper ini juga bertujuanuntuk membahas cara Tionghoa dalam pembinaan mualaf dan MuslimTionghoa melalui literasi media komunikasi dan teknologi informasi. Melaluimetode analisis media, literasi media komunikasi merupakan bagian darikomunikasi yang berbasis pada siapa bicara apa, kapan, di mana dan melaluimedia apa serta apa dampaknya. Hasil penelitian menunjukkan bahwa literasimedia komunikasi yang digunakan komunitas Tionghoa Muslim di Indonesiamelalui penerbitan majalah Cheng Hoo, WhatsApp Forum PITI Jatim, Website dan Facebook. Semua media tersebut digunakan dan memiliki dampak signifikanbagi relasi, interaksi dan komunikasi antara komunitas Tionghoa Muslimdengan Tionghoa non-Muslim dan komunitas Tionghoa Muslim dengan non-Tionghoa Muslim di negeri ini. Lebih dari itu, cara Tionghoa menjadi Muslimyang baik juga terlihat dalam beberapa pelayanan pendidikan Islam berbasiskomunitas Tionghoa di Indonesia dari Taman Kanak-Kanak, Sekolah DasarIslam, pengajian rutin, dan Pesantren.